Social geographies from difference to action - Panelli, Ruth (London SAGE, 2004)
This accessible textbook is a stimulating introduction to contemporary social geography. It provides students with the tools to understand the various frameworks that geographers use to conceptualize, document, and attempt to overcome social differences.
Includes bibliographical references and index.
Keywords: Social geography; Social geography -- Methodology; Electronic books